Control of Polychaetes by Dipping Infected Pearl Oyster on Different Salinity - Hadiroseyani, Yani; Iswadi, .; Djokosetyanto, Daniel (Jurnal Akuakultur Indonesia, 2004)
Dip treatment on pearl oysters (Pinctada maxima) was conducted in different concentrations of saline water to eliminate boring polychaetes. Results shows that polychaetes leave the oysters which treated on saline water at 0 ppt, 45 ppt, and 60 ppt as long as 15 minutes each. It also shows that the oysters got high survival rate 7 days after the treatment. Key words: Pearl oyster, Pinctada maxima, polychaetes, salt, dipping, survival rate